Improvement of irritable bowel syndrome with glucagon like peptide-1 receptor agonists: a systematic review and meta-analysis - Mostafa, Mohamed E. A.; Alrasheed, Tariq (Frontiers in Endocrinology, 2025)
IntroductionIrritable bowel syndrome (IBS) is a severe gastrointestinal condition with symptoms like pain, bloating, diarrhea, and constipation. Glucagon-like peptide-1 (GLP-1) receptors, expressed in the central nervous system and peripheral tissues, have been found to affect gut motility. GLP-1 and its analog ROSE-010 have been shown to inhibit the migrating motor complex and decrease gastrointestinal motility in IBS patients.AimThis systematic review and meta-analysis aim to assess the efficacy and safety of GLP-1 receptor agonists in providing pain and symptom relief for individuals with IBS.MethodsThe study conducted extensive searches across various databases, including Cochrane Library, Web of Science, PubMed, Google Scholar, and Science Direct, to identify studies on IBS and related drugs. A search strategy using keywords and medical subject heading terms (MeSH) was developed to ensure inclusivity. Exclusion criteria included non-English language studies, books, conference papers, case reports, in vitro studies, animal studies, and non-original articles.ResultsThe study found that ROSE-010 (100 µg) significantly lowered pain intensity in IBS patients compared to a placebo, with an overall odds ratio of 2.30, 95% CI: 1.53-3.46. ROSE-010 (300 µg) is more effective than a placebo for all irritable bowel syndrome subtypes, with consistent effects across trials. ROSE-010 is linked to a greater incidence of nausea, vomiting, and headache than placebo.ConclusionROSE-010, a glucagon-like peptide-1 receptor agonist, has been shown to reduce pain in individuals with IBS. However, its higher frequency of nausea, vomiting, and headache suggests the need for close monitoring and individualized treatment plans. Further investigation is needed to understand its impact on different IBS subtypes and long-term effects.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024613545.